2010
DOI: 10.1016/j.juro.2010.06.097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Laparoscopic Renal Surgery Mini-Fellowship Program on Postgraduate Urologist Practice Patterns at 3-Year Followup

Abstract: An intensive 5-day laparoscopic ablative and reconstructive renal surgery course enabled postgraduate urologists to effectively introduce and expand the volume and breadth of their laparoscopic renal surgery practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Concomitantly, participants performed hand-assisted laparoscopic surgery considerably less often ( P = 0.008)[40]. In a large sample including 106 urologists, Kolla et al[41] reported similar findings to those described before. In a study evaluating the impact of 5-d mini fellowship program that included tutorial sessions, hands-on inanimate and animate skills training, and clinical case observations, there was also a significant increase in the laparoscopic procedures performed by the participants after the program.…”
Section: Impact Of Laparoscopic Training Coursesmentioning
confidence: 56%
“…Concomitantly, participants performed hand-assisted laparoscopic surgery considerably less often ( P = 0.008)[40]. In a large sample including 106 urologists, Kolla et al[41] reported similar findings to those described before. In a study evaluating the impact of 5-d mini fellowship program that included tutorial sessions, hands-on inanimate and animate skills training, and clinical case observations, there was also a significant increase in the laparoscopic procedures performed by the participants after the program.…”
Section: Impact Of Laparoscopic Training Coursesmentioning
confidence: 56%
“…37 This concern has been recognized by both the urology and surgery communities, and, in recent years, several mentored and simulator-based programs have been developed to facilitate and enhance training in laparoscopy. 38,39 Nonetheless, despite the existence of recommended paradigms for laparoscopic training and credentialing since the early 1990s, training in laparoscopy still relies heavily on preceptorship and self-regulation rather than any formal certification process while credentialing varies by hospitals and generally involves limited regulatory oversight. [40][41][42] Similar challenges are now being recognized during the adoption of the robotic platform in surgical oncology.…”
Section: Discussionmentioning
confidence: 99%
“…43 More vigorous training has been shown to expedite the learning process, transfer technical skill at a higher rate, and lead to higher retention over the longterm. 39,[44][45][46] To promote the advancement of patient care through new surgical technologies while also ensuring patient safety, the American College of Surgeons has established multiple Accredited Education Institutes to facilitate transfer of surgical innovation to practicing surgeons, [47][48][49] similar programs may be beneficial for urologists and other surgical oncologists who are faced with the challenge of adopting complex new technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Five-day minifellowship/miniresidency courses have been proven to provide urologic surgeons with an effective introduction and uptake of laparoscopic urology. 12 The Japanese Society of Endourology and ESWL have established the Endoscopic Surgical Skill Qualification System in urologic laparoscopy. 13 In the Japanese model, the mentees must have completed 2 years of laparoscopic training, performed 20 laparoscopic procedures, and are then independently assessed by two expert referees who view unedited videotapes showing the entire laparoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%